Basic Electrical and electronics engineering-I - Chakrabarti, Abhijit (Tata McGraw Hill, 2013)
Basic Electrical and electronics engineering-I / Chakrabarti, Abhijit. -- New Delhi: Tata McGraw Hill, 2013